Evaluación técnica de la recuperación ambiental del suelo por derrame de petróleo crudo mediante la aplicación de la tecnología oil spill eater II en un pozo de un bloque en el Casanare (2020)
Crude oil spills aren´t inevitable, it depends of internal or external factors of the oil industry; taking this into account we decide to developed a strategy that will allow a timely and efficient response in the future, based on a real case that took place in a well located in Casanare Colombia, where OIL SPILL EATER II technology was used for the environmental recovery of the soil contaminated by oil. In order to validate the veracity and effectiveness of the care provided and the technology since the intervention of the spill and the development of this text, we verify the laboratory tests of the soil to determinate the content of oils and fats, benzene, HAP'S, total petroleum hydrocarbons (TPH), BTEX sum and toluene; governed under Louisiana 29B to determinate the soil status. These tests were related and evaluated with the results of the operating company and the service provider that evidenced the efficient recovery of the soil, since the percentages of TPH, the main parameter to measure soil remediation process, reach values lower than required, at the end of the intervention and one year after the contingency.